STRUKTUR ANATOMI ORGAN VEGETATIF DARUJU (Acanthus spp.) DI HUTAN MANGROVE KENAGARIAN MANGGUANG KOTA PARIAMAN - Safitri, Desviana; Eka Putri, Irma Leilani; Amri, Erismar (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ A study on anatomical structure of the vegetativeâsÂ Â organ was taken on Acanthus spp. based on differents leaf morphological. The samples was taken from Mangguangâs Mangrove, Pariman that has found seven leaves morphology variation of Acanthus spp. and semi permanent anatomy preparation was made in Plant Structure and Development laboratory of Andalas University. The purpose of this research was to describe anatomical structure of roots, steams, and leaves of Acanthus spp. The result has shown anatomical structure of roots, steams, and leaves from seven leaves variation of Acanthus spp. The transverse section of Acanthus Â spp. Â rootsÂ composedÂ ofÂ epidermis, Â cortex, Â aerenchyma,Â andÂ stele (xylem and phloem with fibers), but last variation has periderm. The transverse section of all variation Acanthus spp. steams composed of epidermis, cortex, collenchyma, clorenchyma, parenchyma, endodermis, phloemâs fibers, vascular bundles (xylem and phloem) with collateral type, and empulur parenchyma. The tranverse section of Acanthus spp. leaves composed of cuticle, epidermis, salt glands, one until two layers hypodermis, palisade, spongy, and stomata. The paradermal section of all leaves variation Acanthus spp. shown stomata with diacytic type. That conclusion has shown similarly of anatomical structure altrought has differents leaf morphology.Â Â